Partycypacja społeczna jako filar demokracji środowiskowej w Chińskiej Republice Ludowej - Bazylińska-Nagler, Justyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The latest revision from 2014 of the Chinese Environmental Protection Law introduced a new mechanism of public participation in environmental law-making. It forces the Chinese legislative process to be more transparent and inclusive, that is to say — involve civil society and NGOs. Generally, this development deserves support and approval; there are, however, several shortcomings that should be addressed in the future. For instance, neither the level of cooperation between legislature and civil society nor the outcomes of public participation do always meet social expectations. The purpose of this work was to research the Chinese model of public participation in environmental decision-making, bearing in mind the authoritarian governance of the People’s Republic of China. Then, to analyze the real impact of the international cooperation and standards on the application of this model. Specifically, the EU–China Environmental Governance Programme (2010–2015) was discussed as a very influential example. The outcome of the research shows that Chinese environmental law has been notably shaped by public international and European law. There are considerable similarities between the legal instruments of environmental democracy applied in China and public international law standards promoted by the United Nations and the European Union through the implementation of the Aarhus Convention of 1998. And, without doubt, it has to be recognised that the People’s Republic of China has its own rich and diversified, however contradictory during the course of history, doctrines and a jurisprudence body of work considering civil society’s participatory role in decision-making. Each of the successive Chinese forms of government — beginning with despotism, then a glimpse of democracy, totalitarianism, and, finally, authoritarianism — did leave their mark on the Chinese political thought and law regarding the desired participation level of society (i.e. various civil movements and NGOs) in state affairs. In this day and age, social interest and support for the environmental protection is well-accepted by the Chinese government, especially due to the current plan of the Communist Party of China (CPC) to build an “ecological civilization” in China.
Keywords: demokracja środowiskowa; partycypacja społeczna; społeczeństwo obywatelskie Chińskiej Republiki Ludowej; autorytaryzm; totalitaryzm; środowiskowe NGO’s; Program zarządzania środowiskiem UE–Chiny